Body Image Satisfaction and Quality of Life among Aesthetic Surgery Clients - Raghda Abdulzahra Khudair, Iman Hussein Alwan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A negative body image contributes to poor quality of life, which can lead to more susceptible to many disturbances in physical, psychological and social. The aimed to investigate the relationship body image satisfaction and its relationship to quality of life among aesthetic surgery in Babylon Province/ Iraq. Methods: The correlational study design approach is done by interrogating members of the study population is conducted in Babylon Prpvince. To conduct the study, a non-probability (purposive) sample of (150) clientele who attend beauty facilities in Babylon Province was chosen. The contentment with one’s body image is addressed in the used questionnaire. The questionnaire’s dependability was established through a pilot research, and it was subsequently presented to experts for validation. The information was gathered through interview techniques and analyzed using descriptive and inferential statistical data analysis. Results: Out of 150 participants aged 20-25 years at mean age is 26 (±4.98), the female clients predominated (82.7%), urban residents (86.0%), the single clients were composed the highest percentage (60.7%), the students clients were constituted the majority (92.0%), clients hasn’t had any previous plastic surgery (72.7%), clients wants to have a rhinoplasty (50.7%) to improve their appearance (89.3). There were significant correlation (positive) between body image and quality of life (r=0.168; p=0.040), and simple liner regression confirmed that the body image had been affected quality of life. Conclusions: A negative body image contributes to poor quality of life, which can lead to more susceptible to many disturbances in physical, psychological and social. Body image dissatisfaction is associated with marked impairment in aspects of quality of life relating to mental health and psycho-social functioning and at least some aspects of physical health. It is need to be counseling program to attain a realistic, positive perception of their body image and to overcome the negative views about their body image in order to enhance their self-esteem and different dimensions of their quality of life.